Manipulating Fiscal Forecasts: Evidence from the German States - Björn Kauder; Niklas Potrafke; Christoph Schinke (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine whether German state governments manipulated fiscal forecasts before elections. Our data set includes three fiscal measures over the period 1980-2014. The results do not show that electoral motives influenced fiscal forecasts in West German states. By contrast, East German state governments underestimated spending in pre-election years (compared to other years) by about 0.20 percent of GDP, tax revenues by about 0.36 percent of GDP, and net lending by 0.30 percent of GDP. Predicting low levels of spending and tax revenues, East German state governments thus underestimated the size of government in pre-election years.
Keywords: H68; E32; E62; 330; fiscal forecasts; electoral cycles; East and West Germany